Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share Terhadap Hasil Belajar IPA Biologi Pada Siswa Kelas VIII SMP Negeri 7 Palu - Indhira Mardiana; Mursito S. Bialangi; Gamar B.N Shamdas; Bustamin; Raya Agni; Mohammad Jamhari (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to describe the effect of the Think Pair Share (TPS) cooperative learning model on the science learning outcomes of eighth-grade students at SMP Negeri 7 Palu. This study used a quasi-experimental design with a pretest-posttest control group design. The population of this study consisted of all eighth-grade students in six classes, with a total of 166 students. The sample of this study consisted of classes VIII A and VIII B, with a total of 54 students. The sampling technique used was purposive sampling, whereby both classes were selected as sample classes because they were relatively homogeneous in terms of student grades, numbers, and characteristics. The data collection technique was a test. The instrument in this study was a learning outcome test used for pretest and posttest. Instrument testing included validity and reliability tests, while assumption testing included normality and homogeneity tests. Hypothesis testing used an independent samples t-test and learning outcome improvement was tested using an N-Gain test. The results showed that there was a significant effect of the TPS cooperative learning model on biology learning outcomes in grade VIII students at SMP Negeri 7 Palu. The average posttest score for the experimental class was 76, while that for the control class was 39. The N-Gain test results showed a higher increase in learning outcomes in the experimental class with a score of 0.72, which is in the high category. In conclusion, the TPS cooperative learning model has a significant effect on biology learning outcomes.